Dealing with cultural elements in technical texts for translation - Stolze, Radegundis (The Journal of Specialised Translation, 2009)
Culture is the background of every human communication. Cultural embedding as a feature of texts in general is also valid in technical and scientific texts. As translation by humans is based on understanding, the translator needs knowledge in order to detect cultural aspects. This is possible by putting down implicit cultural references to certain structures on the text level. Cultural elements appear in the text on all levels – from the concept and form of words, to the sentence and text structure, to pragmatics. Examples for the various appearances are presented in the first part of the paper.The second part discusses translation as a writing process. Here the categories of attention governing the translator's approach are presented. Taking a holistic view of the text, the translator may consider the relevant cultural context, discourse field, conceptual world and predicative mode to promote his or her understanding. The target language formulation will then observe the medium, stylistics, coherence and function of the text. Dealing with cultural elements may be motivated in view of the aforementioned categories of attention.